1991
DOI: 10.1007/bf00183460
|View full text |Cite
|
Sign up to set email alerts
|

Ion channels formed by amphipathic helical peptides

Abstract: Channel forming peptides (CFPs) are amphipathic peptides, of length ca. 20 residues, which adopt an alpha-helical conformation in the presence of lipid bilayers and form ion channels with electrophysiological properties comparable to those of ion channel proteins. We have modelled CFP channels as bundles of parallel trans-bilayer helices surrounding a central ion-permeable pore. Ion-channel interactions have been explored via accessible surface area calculations, and via evaluation of changes in van der Waals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 42 publications
1
29
0
Order By: Relevance
“…In this study, we show that the EXXP motif located upstream of VXXLL in BAR also contributes to the interaction of Mfa with (1,15,35,36). In these proteins, the Pro residue confers a kink within an ␣-helical region, and Sansom et al (30,31) suggested that an acidic residue at position ÏȘ3 from Pro may function in cation binding. Consistent with this, Duan et al (13) showed that the S. gordonii antigen I/II protein, SspB, binds calcium and that the BAR region of antigen I/II was necessary for cation binding activity.…”
Section: Discussionmentioning
confidence: 57%
“…In this study, we show that the EXXP motif located upstream of VXXLL in BAR also contributes to the interaction of Mfa with (1,15,35,36). In these proteins, the Pro residue confers a kink within an ␣-helical region, and Sansom et al (30,31) suggested that an acidic residue at position ÏȘ3 from Pro may function in cation binding. Consistent with this, Duan et al (13) showed that the S. gordonii antigen I/II protein, SspB, binds calcium and that the BAR region of antigen I/II was necessary for cation binding activity.…”
Section: Discussionmentioning
confidence: 57%
“…Additional arguments that can be employed to rationalize the departure of the kinetics shown in Fig. 3, panel a, from a simple mono-exponential-like curve stem from the fact that even in the absence of the potential difference across the lipid membrane, the alamethicin peptide adopts two kinds of orientations: a tilted orientation at the membrane-aqueous solution interface, and a more fully transmembrane-inserted orientation, with the N terminal almost reaching to the trans side of the membrane [25,26]. Although the alamethicin monomers in this latter orientation are very unlikely to attain the 'critical concentration' needed generate transmembrane conductive oligomers, they may also contribute to the overall changes of the dipole potential (Δp) of the membrane.…”
Section: Resultsmentioning
confidence: 99%
“…For interhelix restraints, dTARGET = 9.4 A in all models. An asymmetric biharmonic potential able in several studies of TM helix bundles, 13, 24 and is comparable to that employed by Nilges and Briinger in simulations of GCN4 helix dimen2' …”
Section: Alm-l2mentioning
confidence: 85%